PENGGUNAAN CHAT GPT SEBAGAI SUMBER BELAJAR MANDIRI DALAM MATA PELAJARAN BAHASA INDONESIA SISWA KELAS X JURUSAN DESAIN PERMODELAN DAN INFORMASI BANGUNAN SMKN 2 BONE - Asniana; Andi Suharman; Andi Hajar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence (AI) technology has introduced various innovations in education, one of which is the use of ChatGPT as an independent learning resource. This study aimed to describe the use of ChatGPT as an independent learning resource in Indonesian language learning among tenth-grade students of the Building Modeling and Information Design (DPIB) Department at SMKN 2 Bone. This research employed a qualitative approach with a descriptive research design. The participants consisted of eight students selected through purposive sampling based on their active use of ChatGPT in Indonesian language learning. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that students used ChatGPT to search for information, understand learning materials, obtain text examples, summarize lessons, and complete learning assignments. The use of ChatGPT provided quick, practical, and flexible access to information, thereby enhancing students' understanding of learning materials, learning motivation, and independent learning skills. However, several challenges were identified, including unstable internet connections, responses that were sometimes too lengthy or less relevant to students' needs, and the tendency of some students to rely on instant answers without verifying the information. Therefore, the use of ChatGPT as an independent learning resource should be accompanied by teacher guidance to ensure that it is used critically, responsibly, and in accordance with educational objectives.